2016
DOI: 10.1039/c6cp05867a
|View full text |Cite
|
Sign up to set email alerts
|

Calculations of the active mode and energetic barrier to electron attachment to CF3 and comparison with kinetic modeling of experimental results

Abstract: To provide a deeper understanding of the kinetics of electron attachment to CF, the six-dimensional potential energy surfaces of both CF and CF were developed by fitting ∼3000 ab initio points per surface at the AE-CCSD(T)-F12a/AVTZ level using the permutation invariant polynomial-neural network (PIP-NN) approach. The fitted potential energy surfaces for CF and CF had root mean square fitting errors relative to the ab initio calculations of 1.2 and 1.8 cm, respectively. The main active mode for the crossing be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Extensive calculations were conducted to test for direct nucleophilic reactivity of the pentacoordinate anions B and D . All calculations revealed that direct transfer of CF 3 from the silicon center to an electrophile requires concomitant inversion of the CF 3 , with a prohibitively large barrier (>100 kcal mol –1 ; in line with the barrier for inversion of the free CF 3 anion) . The pentacoordinate siliconate anions thus act as reservoirs, not active nucleophiles, liberating free (non-silicon-coordinated) CF 3 – via dissociation.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Extensive calculations were conducted to test for direct nucleophilic reactivity of the pentacoordinate anions B and D . All calculations revealed that direct transfer of CF 3 from the silicon center to an electrophile requires concomitant inversion of the CF 3 , with a prohibitively large barrier (>100 kcal mol –1 ; in line with the barrier for inversion of the free CF 3 anion) . The pentacoordinate siliconate anions thus act as reservoirs, not active nucleophiles, liberating free (non-silicon-coordinated) CF 3 – via dissociation.…”
Section: Resultsmentioning
confidence: 74%
“…[X – ] 0 sets the initial concentration of the siliconate ([ D ] 0 = (1 – x EI )[X – ] 0 ), 60 which, in the absence of endogenous inhibitors, is essentially constant throughout the reaction. The insurmountable barrier for CF 3 inversion 67 means that, independent of the identity of the electrophile, E , or proton donor, R–H, the siliconate is unable to effect direct anionic trifluoromethyl transfer, Figure 10 i. In all cases, the reaction must proceed via a dissociative pathway, Figure 10 ii, in which M + plays a key role: the stronger the association of M + with CF 3 , the more favorable k –3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation